2005
DOI: 10.1007/s00199-004-0497-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and incentive compatibility of Walrasian expectations equilibrium in infinite dimensional commodity spaces

Abstract: We consider a differential information economy with infinitely many commodities and analyze the veto power of the grand coalition with respect the ability of blocking non-Walrasian expectations equilibrium allocations. We provide two different Walrasian expectations equilibrium equivalence results. First by perturbing the initial endowments in a precise direction we show that an allocation is a Walrasian expectations equilibrium if and only if it is not “privately dominated” by the grand coalition. The second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…The main motivation for studying the private core stems from recent literature on differential information economies with a finite number of commodities which has shown several interesting properties of this solution concept: it is non-empty under standard continuity and concavity assumptions (Yannelis (1991), and Einy, Moreno and Shitovitz (2001)); it is coalitionally incentive compatible and it rewards the informational superiority of traders (Koutsougeras and Yannelis (1993)). The extensions of these properties to infinite dimensional models are discussed in Hervés-Beloso, Moreno-García and Yannelis (2005b) and Meo (2002).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The main motivation for studying the private core stems from recent literature on differential information economies with a finite number of commodities which has shown several interesting properties of this solution concept: it is non-empty under standard continuity and concavity assumptions (Yannelis (1991), and Einy, Moreno and Shitovitz (2001)); it is coalitionally incentive compatible and it rewards the informational superiority of traders (Koutsougeras and Yannelis (1993)). The extensions of these properties to infinite dimensional models are discussed in Hervés-Beloso, Moreno-García and Yannelis (2005b) and Meo (2002).…”
Section: Introductionmentioning
confidence: 94%
“…Therefore, it applies to infinite-dimensional commodity spaces, even if the Lyapunov convexity theorem does not hold, provided that the separability assumption is satisfied. Note that, in Hervés-Beloso, Moreno-García and Yannelis (2005b), a characterization of Radner equilibria via privately nondominated allocations is provided when the space of commodities is l ∞ endowed with the Mackey topology by using a approach like that of Vind.…”
Section: Theorem 52 Assume That the Economy E Satisfies (A1)-(a4)mentioning
confidence: 99%
“…Finally, we will say that an allocation x is private c-fair relative to T 1 and T 0 if it is private c-fair relative to S 1 and S 2 , for all S 1 ∈ T 1 and S 2 ∈ T 0 . From an Aubin-like perspective, the notion of generalized coalition is as follows (compare [9], [10], [12], [13]). Definition 2.9.…”
Section: Vol 7 (2010)mentioning
confidence: 99%
“…We will assume that relevant allocations are measurable with respect to the private information of agents: that is, no coalition whose members use only their private information, could redistribute the net trade of any other disjoint coalition in a way which would assign a preferred bundle to each of its members. This allows us to compare c-fair allocations with the private core introduced by Yannelis [21] and the Aubin private core introduced in [9], [10] and [12]. As a first consequence, we get characterizations of Walrasian expectations equilibria in terms of suitable notions of coalitionally fair allocations, even when the set of large traders is non empty.…”
Section: Introductionmentioning
confidence: 99%
“…In Hervés-Beloso et al (2005a, 2005b, we provide characterizations of Walrasian allocations in terms of the blocking power of the "society" called "grand coalition." Precisely, in Hervés-Beloso et al (2005b), it is shown that the set of Walrasian allocations coincides with the set of allocations which are not blocked, in the sense of Aubin, by the society. Therefore, in order to obtain the equilibria it suffices to consider the Aubin blocking power of just one coalition, namely, the society formed by all the individuals in the economy.…”
Section: Introductionmentioning
confidence: 99%